2017
DOI: 10.1016/j.ebiom.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

p32 is Required for Appropriate Interleukin-6 Production Upon LPS Stimulation and Protects Mice from Endotoxin Shock

Abstract: Sepsis is a major cause of morbidity and mortality in seriously ill patients and mitochondrial dysfunction is associated with poor outcomes in septic patients. Although interleukin-6 (IL-6) is a good prognostic marker for sepsis, the relationship between mitochondrial dysfunction and IL-6 remains poorly understood. We identified p32/C1QBP/HABP1 as a regulator of IL-6 production in response to lipopolysaccharide (LPS). LPS induced IL-6 overproduction in p32 deficient mouse embryonic fibroblasts (MEFs) through N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In summary, our study has identified the mitochondrial protein p32 as an important factor for metabolism and maturation in DCs. Recent studies on mice revealed that p32 is involved in cardiomyopathy (Saito et al, 2017), innate immunity (Sasaki et al, 2017), and obesity (Liu et al, 2017). Moreover, p32 mutations are associated with a clinical spectrum ranging from infantile lactic acidosis to childhood cardiomyopathy and late-onset progressive external ophthalmoplegia in humans (Feichtinger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our study has identified the mitochondrial protein p32 as an important factor for metabolism and maturation in DCs. Recent studies on mice revealed that p32 is involved in cardiomyopathy (Saito et al, 2017), innate immunity (Sasaki et al, 2017), and obesity (Liu et al, 2017). Moreover, p32 mutations are associated with a clinical spectrum ranging from infantile lactic acidosis to childhood cardiomyopathy and late-onset progressive external ophthalmoplegia in humans (Feichtinger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our group showed that p32 is processed by proteolytic cleavage of N-terminal amino acids containing a mitochondrial signal sequence (Muta et al, 1997) and is essential for mouse embryonic development dependent on mitochondrial translation (Yagi et al, 2012). In addition, using macrophages and mouse embryonic fibroblasts (MEFs), we demonstrated that p32 is required for appropriate interleukin (IL)-6 production upon lipopolysaccharide (LPS) stimulation (Sasaki et al, 2017). Recent studies showed that p32 mutations impair the mitochondrial respiratory chain and cause cardiomyopathy in humans and mice (Feichtinger et al, 2017;Saito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ATF4 is a member of the activating transcription factor family and is essential in many biological mechanisms, such as in the stress response, medullary hematopoiesis and bone resorption (Ameri and Harris 2008 ). Several studies show that ATF4 participates in inflammatory responses and positively regulates the secretion of pro-inflammatory cytokines such as interleukin (IL)-6, IL-8 and interferon γ (Iwasaki et al 2014 ; Sasaki et al 2017 ; Zhang et al 2013 ). Furthermore, a genome-wide association study (GWAS) suggested that a region in the proximity of the MED13L gene is associated with type 1 diabetes (Wellcome Trust Case Control Consortium 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…ATF4 has been shown to be induced by multiple types of stimuli. For example, Sasaki et al [17] identified ATF4 as a mediator of IL-6 expression induced by LPS in embryonic fibroblast cells of p32 deficient mouse. Hara et al [32] identified that ATF4 mediated IL-23 p19 mRNA expression induced by LPS in a JNK-dependent manner, which could be inhibited by apomorphine.…”
Section: Discussionmentioning
confidence: 99%
“…Human corneal epithelial cells (HCECs) were provided by the Ocular Surface Laboratory at the Zhongshan Ophthalmic Center. Cells were cultured to 80% confluence in serum-free DMEM (HyClone, USA) for 24 hours and then treated in 6-well plates with 100 ng/mL lipopolysaccharide (LPS) (Sigma-Aldrich, USA) [17], 5 µ g/mL β -1, 3-glucan (Santa Cruz, USA) [18], 1 ng/mL transforming growth factor beta (TGF- β ) (ProSpec, Israel) [19], 10 ng/mL interleukin 1 beta (IL-1 β ) (ProSpec, Israel) [19], and A. fumigatus conidia at a multiplicity of infection (MOI) of 1 for 8 and 16 hours. These cells were then used in western blot assay.…”
Section: Methodsmentioning
confidence: 99%